Potentially inappropriate prescription of medications to older adults who access a community pharmacy in Peru - Mónica Bazán-Vásquez; Gladys Galliani-Huamanchumo; Alessandra Campos-Bazán; Haydee Villafana-Medina; Kelyn Requejo-Torres; Julio Campos-Florián (Pensoft Publishers, 2024)
Polypharmacy in older adults is associated with a higher incidence of medication-related problems, such as pharmacological interactions, adverse reactions, and medication errors. This study aimed to identify and evaluate potentially inappropriate prescription of medications (PIP) using the screening tool of older persons' prescriptions/screening tool to alert doctors to right treatment (STOPP/START) criteria in a representative community pharmacy in Trujillo, Peru. The population sample consisted of 158 subjects, with 66.5% between 65 and 69 years old, 53.8% male, and 77.9% receiving between 3 and 4 medications. Medical prescriptions were analyzed using the explicit STOPP/START version 2 criteria, revealing that 93.7% of patients presented STOPP criteria (to stop medication) and 53.8% presented START criteria (to start medication). The most frequently identified STOPP criterion was the gradual withdrawal of benzodiazepines, while the most frequently identified START criterion was the initiation of antihypertensive treatment in patients with systolic blood pressure > 160 mmHg and diastolic blood pressure > 90 mmHg. Principal component analysis showed that the high prevalence of PIP was significantly associated (p < 0.05) with the number of prescribed medications and as age decreases, the number of medical diagnoses also decreases. It is concluded that there is a high prevalence of PIP in the studied population, posing a greater challenge in older adults, highlighting the importance of addressing prescribing practices with greater involvement of community pharmacists.